A rare case of cerebellar pilomyxoid astrocytoma associated with neurofibromatosis-1 in a young female; case report highlighting immunohistochemical features - Siddhi Gaurish Sinai Khandeparkar; Shital Subhash Gosavi; Bageshri P Gogate; Nikhil Talathi (Wolters Kluwer Medknow Publications, 2021)
Pilomyxoid astrocytoma (PMA), a distinct clinico-histopathological entity in the World Health Organization classification 2007, tends to be locally aggressive, with higher chance of leptomeningeal dissemination, recurrence, and poor prognosis. PMA is generally seen in young children and tend to occur in the hypothalamic-chiasmatic region. Their presence in other parts of the brain in the non pediatric age group is uncommon. To the best of our knowledge we are presenting first case of cerebellar PMA associated with neurofibromatosis 1 (NF1) in a 40-year- old female, with immunohistochemical study.